2004
DOI: 10.1111/j.1083-4389.2004.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Helicobacter pylori‐Induced Gastritis and the Effect of H. pylori Eradication in Patients with Chronic Idiopathic Thrombocytopenic Purpura

Abstract: H. pylori-infected ITP patients have a corpus-predominant pattern of gastritis but the virulence profile of their strains does not differ from that of ulcer or NUD patients. Eradication of H. pylori infection is a good therapeutic option for some patients with chronic ITP, especially for those who develop ITP in older age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 52 publications
(70 reference statements)
2
39
0
Order By: Relevance
“…Platelet recovery was found in patients previously refractory to immunosuppression or splenectomy, as reported by others. 7,40 We also observed a response rate of 71% in patients with a severe form of ITP (platelets Ͻ 30 ϫ 10 9 /L), similar to that of other reports, 7,40 whereas minor 41 or nearly negative 10 results were also reported.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Platelet recovery was found in patients previously refractory to immunosuppression or splenectomy, as reported by others. 7,40 We also observed a response rate of 71% in patients with a severe form of ITP (platelets Ͻ 30 ϫ 10 9 /L), similar to that of other reports, 7,40 whereas minor 41 or nearly negative 10 results were also reported.…”
Section: Discussionsupporting
confidence: 90%
“…infection in our series is not higher than that (58%) in the general population of the area of Modena province, 36 or that (67%) in healthy Italian blood donors aged 50 years or older, 37 in keeping with the data from the other countries, where the prevalence of infection in patients with ITP is similar or lower than that of the general population of the same area, 6,10,13,38,39 with rare exceptions. 15,40 In our study, we observed a platelet improvement in 68% of patients with eradicated infection (60.5% of patients infected; 30.6% of total patients with ITP); in about 1500 patients so far reported in the literature, including the 3 US and Spanish cohorts with the lowest responses, the rate of response was about 53%. 17 The highest response rate was reported in cohorts from Italy, Japan, and the United Kingdom.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations